(untitled) (Scientific Journal of the Dragomanov Ukrainian State University Series 2 Computer-Oriented Learning Systems, 2025)
The article examines the possibilities of applying information technology infrastructure monitoring systems in the training of future specialists in information technologies at higher education institutions. It is emphasized that in the context of the digital transformation of education, the development of distance and blended learning, as well as the increasing complexity of university IT infrastructures, the need for modern tools for controlling and managing technical resources is growing. It is substantiated that the use of IT infrastructure monitoring systems is not only a technological solution for ensuring the stable operation of servers, network equipment, or cloud services, but also an effective educational tool that enables learners to develop practical competencies necessary for professional activities in the field of information technologies. The article provides a comparative analysis of widely used monitoring systems – Nagios, Icinga, Prometheus, Grafana, and Zabbix – considering their technical capabilities, usability, potential for integration into the educational environment, and didactic effectiveness. It is shown that Zabbix is distinguished by its versatility, extensive set of agent-based and agentless data collection methods, advanced trigger and notification mechanisms, capabilities for dashboard creation, administration automation, and simulation of real-world operational scenarios. Attention is paid to the development of Zabbix-based learning environments for monitoring servers, containerized systems, virtualization platforms, data storage infrastructures, and network services. Examples of integrating Zabbix into educational disciplines such as “System Administration,” “Data Protection,” “Administration of Computer Systems and Networks,” and “Web-Oriented Educational Computer Systems” are presented, with an emphasis on fostering analytical thinking and practical skills in using industry-level tools. It is demonstrated that the implementation of Zabbix in the educational process contributes to improving the quality of professional training, develops learners’ ability to work with complex IT infrastructures, and ensures the integration of theoretical knowledge with practical activities in conditions closely resembling real industrial environments.